Evaluating Cardiovascular Risk: Lipid Profile Changes Due to Pesti-cide Exposure in Agricultural Sprayers - A Case-Control Study - Nawaz, Alina; Maqsood, Kaleem; Liaqat, Farwa; Nizam, Naira; Roohi, Nabila (BioScientific Review, 2025)
Introduction. There are several threats to the human body from the potentially hazardous chemicals used in crop fields, such as pesticides. This investigation aims to assess variations in the serum lipid profile associated with pesticide exposure. Methodology. For this case-control study, 131 participants were recruited. These included 71 pesticide sprayers and 60 healthy individuals who served as the control group, all from the rural areas of South Punjab, Pakistan. The lipid biomarkers of the participants were evaluated using a biochemistry analyzer and the results were statistically analyzed through GraphPad Prism. Results. The results indicated that TG (triglycerides) and TC (total cholesterol) levels significantly (p<0.001) increased with a prominent increase in LDL-C (low-density lipoprotein cholesterol) and VLDL-C (very low-density lipoprotein cholesterol) (p<0.001 and 0.011 respectively). However, a significant decrease in HDL-C (high-density lipoprotein cholesterol) (p=0.006) was observed in sprayers as compared to the control group. Conclusion. These alterations may be attributed to oxidative stress and hepatic dysfunction induced by prolonged pesticide exposure. The results are based on the hypothesis that significant alterations in the lipid profile anticipate potential health risks associated with pesticide exposure. Introduction. There are several threats to the human body from the potentially hazardous chemicals used in crop fields, such as pesticides. This investigation aims to assess variations in the serum lipid profile associated with pesticide exposure. Methodology. For this case-control study, 131 participants were recruited. These included 71 pesticide sprayers and 60 healthy individuals who served as the control group, all from the rural areas of South Punjab, Pakistan. The lipid biomarkers of the participants were evaluated using a biochemistry analyzer and the results were statistically analyzed through GraphPad Prism. Results. The results indicated that TG (triglycerides) and TC (total cholesterol) levels significantly (p<0.001) increased with a prominent increase in LDL-C (low-density lipoprotein cholesterol) and VLDL-C (very low-density lipoprotein cholesterol) (p<0.001 and 0.011 respectively). However, a significant decrease in HDL-C (high-density lipoprotein cholesterol) (p=0.006) was observed in sprayers as compared to the control group. Conclusion. These alterations may be attributed to oxidative stress and hepatic dysfunction induced by prolonged pesticide exposure. The results are based on the hypothesis that significant alterations in the lipid profile anticipate potential health risks associated with pesticide exposure.